The The independent any of the accomplishments - Rajut Aliskah Cahya; Chientya Annisa Rahman Putrie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2021)
The online learning process is an innovation in learning at the covid-19 process aimed at avoiding the spread of covid-19's disease on students. The study has made it a goal to know the impact of self literacy (x) on learning achievement (y) at the Islamic school vii classes on social science subjects (IPS). The method used in research is collaborative quantitative. The study USES a sample of 57 students. The conclusion of the study: 1). Linear regression equations obtained y = 55,824 + 0,324x, which means the value y can be predicted through the linear equations. 2). Regression results by 0.324, suggesting that for any increased value of self literacy, the student's performance value increases by 0324. 3) by tests of the significant regression line equality gained, it was at-hit and p-value smaller than 0.05 or ho was denied. By doing so, regression y or x significant or self is associated with the performance of studies of its students. 4) the result of the significant coefficient of correlating obtained by 0820 with a small p-value of 0.05, means the ho was denied. Thus the coefficient correlation x or y means significant. While the coefficient determinations obtained are r-square = 0672, which means that 67.2% variable variability of self literacy regarding the performance of the study.